Simple Procedure for the Isolation of Mesenchymal Stem Cells from Different Parts of the Human Umbilical Cord - Suyoko, Ahmad; Prasetyaningrum, Pekik Wiji; Septisetyani, Endah Puji (Indonesian Journal of Cancer Chemoprevention, 2022)
The umbilical cord and placenta are both sources of mesenchymal stem cells (MSCs) that are promising for cell-based therapy. Furthermore, compared to other MSCs sources, they are easy to obtain with no invasive procedures. This study presents an adapted method for stem cell isolation from three different parts of the human umbilical cord, including Wharton’s jelly (WJ), cord lining (CL), and cord-placenta junction (CPJ). The isolation consists of sample preparation, tissue dissection into distinct anatomical regions, mincing and enzyme digestion, and explant culturing. In addition, we monitored when the cells migrated from the explant to the bottom of the cell culture dish and passed the cells after they became confluent. This study found that WJ cells were the first to reach confluence at Passage 0 (P0). In contrast, CL cells needed the longest time to get confluence at P0 but displayed faster cell growth after subsequent passages (P1-P2). In addition, CPJ cells showed growth retardation after P1 and P2. Altogether, we could extract the MSCs from umbilical cord tissue explants by using DMEM supplemented with 10% FBS, 100 IU/mL penicillin, and 100 μg/mL streptomycin as general cell culture medium and omitting the use of gentamicin. However, the MSCs may need a more complex specified medium for optimum cell regeneration for further cell expansion.Keywords: mesenchymal stem cells, umbilical cord, Wharton’s jelly, cord lining, cord-placenta junction.